Perlindungan Hukum Bagi Penumpang Angkutan Umum Trans Serasi Tabanan - I Gusti Agung Tria Masdiana Putra; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2020)
Abstract-Transport is a facility that functions as the transfer of goods or people from one place to another. Seen in the community environment, in fact there are still a number of transporters who carry out actions outside standardization as well as carrying passengers in excess of the prescribed capacity, this has violated traffic rules and violated the rules on consumer protection, In addition, due to the neglected passenger rights and a lack of awareness of passengers in terms of security and comfort as service users, the authors are interested in lifting the title and conducting research on legal protection for public transport passengers at Trans Serasi Tabanan. The problems of this research are; 1. How is legal protection for public transport passengers as consumers of transportation facilities? and 2. What is the responsibility of the carrier for errors that result in losses for public transport passengers? This research is categorized into empirical research, because it wants to know the form of legal protection for Trans Serasi Tabanan passengers. From the results of the research and discussion show that the lack of awareness of the transporters in paying attention to the safety and comfort of passengers and passengers is also less aware of the importance of their rights to obtain security and comfort in using public transportation services so that their rights as service users are ignored.This legal research is expected for the transporters to pay more attention to the comfort and safety of passengers and the passengers are also more selective in using public transport services so that there are no events that can cause harm in any form. Keywords: Legal Protection; Passenger; Public transportation Abstrak-Angkutan merupakan sarana yang berfungsi sebagai pemindah barang ataupun orang dari suatu tempat ke tempat lainnya. Dilihat dalam lingkungan masyarakat, kenyataanya masih ada beberapa oknum pengangkut yang melakukan tindakan diluar standarisasi seperti halnya mengangkut penumpang dalam jumlah melebihi kapasitas yang telah ditetapkan , hal ini sudah melanggar tata tertib dalam berlalu lintas serta melanggar tata tertib tentang perlindungan konsumen. Selain itu, adanya hak-hak penumpang yang terabaikan serta kurangnya kesadaran penumpang dalam hal keamanaan dan kenyamanan sebagai pengguna jasa, maka penulis tertarik mengangkat judul dan melakukan penelitian mengenai perlindungan hukum terhadap penumpang angkutan umum Trans Serasi Tabanan. Adapun permasalahan dari penelitian ini yakni; 1. Bagaimanakah upaya perlindungan hukum terhadap penumpang angkutan umum sebagai konsumen fasilitas transportasi? serta 2. Bagaimanakah tanggung jawab pihak pengangkut terhadap kesalahan yang mengakibatkan kerugian bagi penumpang angkutan umum? Penelitian ini dikategorikan ke dalam penelitian empiris, dikarenakan ingin mengetahui bentuk perlindungan hukum bagi penumpang Trans Serasi Tabanan. Dari hasil penelitian dan pembahasan menunjukkan bahwa kurangnya kesadaran dari pihak pengangkut dalam memperhatikan keamanan dan kenyamanan penumpang serta dari pihak penumpang juga kurang menyadari pentingnya hak-hak mereka untuk memperoleh keamanan dan kenyamanan dalam menggunakan jasa angkutan umum sehingga hak mereka sebagai pengguna jasa pun terabaikan. Penelitian hukum ini diharapkan bagi pengangkut agar lebih memperhatikan kenyamanan dan keamanan penumpang serta pihak penumpang juga lebih selektif dalam menggunakan jasa transportasi angkutan umum agar tidak adanya kejadian yang dapat menimbulkan kerugian dalam bentuk apapun. Kata Kunci: Perlindungan Hukum ; Penumpang ; Angkutan Umum